Routledge Handbook of Asian Borderlands (Taylor & Francis, 2018)
In Asia, where authoritarian-developmental states have proliferated, statehood and social control are heavily contested in borderland spaces. As a result, in the post-Cold War world, borders have not only redefined Asian incomes and mobilities, they have also rekindled neighbouring relations and raised questions about citizenship and security.
English
Keywords: Asia; Asia; borderlands